CO2 utilization: Direct power generation by a coupled system that integrates photocatalytic reduction of CO2 with photocatalytic fuel cell. (July 2019) - Xie, Fengjia; Chen, Rong; Zhu, Xun; Liao, Qiang; Ye, Dingding; Zhang, Biao; Yu, Youxu; Li, Jinwang
Highlights: A coupled system that integrates photocatalytic reduction of CO2 with PFC is developed. Products by photocatalytic reduction of CO2 are directly used as the fuels for PFC. Direct power generation by the coupled system is realized by using CO2 . The feasibility of the coupled system is demonstrated under UV irradiation. Abstract: Carbon dioxide (CO2 ) as greenhouse gas is the primary cause of global warming. One of the ideal routes to remedy CO2 emission is to transform it to hydrocarbons by photocatalytic reduction of CO2 . However, poor yield and product selectivity of photocatalytic reduction of CO2 pose significant challenges to its widespread applications. To address this critical issue, a coupled system that integrates photocatalytic reduction of CO2 with photocatalytic fuel cell (PFC) is developed for direct power generation using CO2 . In this coupled system, the products by photocatalytic reduction of CO2 works as the fuels for the PFC to directly generate electricity. Direct power generation by this coupled system is demonstrated via only in the presence of CO2 as the input under illumination. A short circuit current density of 0.175 mA/cm 2 and a maximum power output of 0.110 mW/cm 2 are yielded for the case with the supply of CO2, which are much higher than those without CO2 . Moreover, it is interesting to find that the fuel concentrations at the PFC outlet are even higher than those at the PFC inlet, implying that the coupled system proposed in this study can not only generate the electricity but also yield the solar fuels. This work opens a new avenue for the CO2 utilization toward direct power generation.